Zwischen Literatur und Naturwissenschaft. Debatten - Probleme - Visionen 1680-1820 - Freiburg, Rudolf (Literatur- und Naturwissenschaften, 2017)
The 18th century witnessed diverse interactions between literature and natural science. Literary texts developed scientific themes, while scientific discourse employed literary techniques. Using representative case studies, this volume examines paradigms and transitions in the history of science (mechanics, geography, botany, chemistry/alchemy) and ways of writing and communicating (the Muses' Almanac, didactic poetry, encyclopedias, etc.).